Outcome of Gynecologic Laparoendoscopic Single-Site Surgery with a Homemade Device and Conventional Laparoscopic Instruments in a Chinese Teaching Hospital. (22nd January 2020) - Su, Xianghui; Jin, Xiaolong; Wen, Canliang; Xu, Qiong; Cai, Chunfang; Zhong, Zhuohui; Tang, Xiang
Abstract : Objective . To demonstrate various benign gynecologic diseases that can be performed by laparoendoscopic single-site surgery (LESS) with conventional laparoscopic instruments. Method . Patients with benign gynecologic diseases that need ovarian cystectomy, fallopian tube resection, or myomectomy were divided into experimental group and control group, and perioperative outcomes of these patients were analyzed. Results . From November 2017 to May 2018, 65 LESS gynecological surgeries were performed, among which there were 25 ovarian cystectomies, 28 unilateral fallopian tube resections, and 12 myomectomies. All the surgeries were completed smoothly, and only one surgery needed one more additional port. No patients have severe complications. Operative time, intraoperative blood loss, and perioperative complications have no difference between the two groups. The LESS laparoscopy group had less postoperative pain scores and longer bowel recovering time, compared with the conventional laparoscopy group (<0.05). Conclusion . Compared with traditional laparoscopy, LESS surgery with conventional laparoscopic instruments is feasible and safe, but postoperative exhaust time is longer than the control group.